A method for preparing a Li10SnP2-xNbxS12-2.5xO2.5x sulfide solid-state battery
Patent Information
- Application Number
- CN202611250208.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]尽管双掺杂可改善硫化物固态电解质性能,但面临元素配比调控难、掺杂剂选择受限、易与锂金属副反应及工艺复杂等挑战,制约实际应用
[0026]本发明的有益效果:本发明通过限定无水溶胶制备体系、精准调控 Nb/O 双掺杂配比与分段热处理工艺,制备出的Li10SnP2-XNbxS12-2.5XO2.5X硫化物固态电解质具备以下优势:
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sulfide all-solid-state battery technology, specifically relating to a Li 10 SnP 2-x Nb x S 12-2.5x O 2.5x Preparation method of sulfide solid-state battery. Background Technology
[0002] With continuous innovation in materials science and electrochemistry, the formulation design and preparation process of sulfide solid electrolytes have been continuously optimized, and significant progress has been made in research. Currently, a variety of novel sulfide solid electrolyte materials have been developed, and their excellent ion conductivity, interfacial compatibility, and processability are becoming increasingly prominent, making them one of the core development directions in the field of future high-energy-density and high-safety batteries.
[0003] For example, patent CN114649562A discloses the preparation and application of a group IIA element and dihalogen-doped sulfide solid electrolyte, whose composition is Li5.5+q+bP1qMqS4.5FbX1.5b (M is one or more of group IIA elements; X is one or more of Cl, Br, and I). The preparation method is as follows: various raw materials are thoroughly mixed in an inert atmosphere, ground, and then ball-milled in a ball mill jar; the ball-milled sample is then pressed into a tablet; finally, the target sulfide solid electrolyte is obtained by sintering.
[0004] For example, patent CN115312843A also discloses a Se-doped solid electrolyte and its preparation method and application, belonging to the field of electrochemical energy storage batteries. This invention, by doping Se into a sulfur-based solid electrolyte, can significantly improve the interfacial stability of the electrolyte and also give it a protective layer effect. After coating the surface of lithium cobalt oxide with the Se-doped solid electrolyte, a uniform coating layer can be formed on the lithium cobalt oxide surface, which can also mitigate the oxygen loss problem of lithium cobalt oxide during high-voltage cycling, allowing the coated lithium cobalt oxide to maintain good Li+ conductivity, and improving its specific capacity and cycle performance.
[0005] Although dual doping can improve the performance of sulfide solid electrolytes, it faces challenges such as difficulty in controlling the elemental ratio, limited dopant selection, easy side reactions with lithium metal, and complex processes, which restrict its practical application. Therefore, a dual doping strategy can be implemented by selecting suitable elements to further improve these shortcomings. Summary of the Invention
[0006] The purpose of this invention is to provide a Li 10 SnP2₋ x Nb x S 12 ₋2.5x O2. 5x The preparation method of sulfide solid-state batteries improves the ionic conductivity and moisture stability of the solid electrolyte and enhances the interfacial compatibility between the electrolyte and the lithium metal anode by optimizing the ratio of anhydrous coordination sol raw materials and segmented heat treatment process, thereby improving the overall cycle performance and service life of the solid-state battery. Nb and O dual-element doping can moderately expand the crystal lattice volume and widen the three-dimensional continuous Li⁺ diffusion channels, effectively improving the bulk ionic conductivity of the electrolyte. Through the matching anhydrous sol preparation and segmented annealing sintering process, atomic-level uniform dispersion of the doping elements can be achieved, reducing side reactions at the electrolyte-lithium metal interface. A dense and stable interfacial passivation layer is generated in situ during cycling, significantly improving the cycle stability and service life of the battery.
[0007] The objective of this invention can be achieved through the following technical solution: A Li 10 SnP 2-x Nb x S 12-2.5x O 2.5x A method for preparing a sulfide solid-state battery, characterized by comprising the following steps:
[0008] (1) Preparation of solid electrolyte: Solid electrolyte was prepared by solid-state sintering with high-purity argon inert atmosphere throughout the process. A stable anhydrous coordination sol was prepared with lithium sulfide (Li2S), phosphorus sulfide (P2S5), tin sulfide (SnS2), niobium pentoxide (Nb2O5), and lithium chloride (LiCl) and phosphorus pentoxide (P2O5).
[0009] (2) Preparation of lithium symmetric battery: To verify the compatibility between the electrolyte and lithium metal, a lithium symmetric battery was assembled, and constant current electrochemical cycle test was carried out at a set current density. The preparation process included the following steps: First, in a glove box filled with argon gas, a certain amount of electrolyte powder was placed in a mold and pressure was applied for cold pressing. Then, the pressed electrolyte sheet was clamped between two lithium metal sheets, and pressure was applied again for pressure holding and sealing. After completion, long-term cycle stability test was carried out.
[0010] As a preferred technical solution of the present invention, in step (1), lithium sulfide Li2S, phosphorus sulfide P2S5, tin sulfide SnS2, niobium pentoxide Nb2O5, lithium chloride LiCl, and phosphorus pentoxide P2O5 are mixed together to prepare a stable anhydrous coordination sol, which is completely isolated from water and oxygen.
[0011] As a preferred technical solution of the present invention
[0012] In step (1), the preparation method of the coordination sol is as follows: • Raw material ratio (parts by mass): EDTA: 11-23 parts; anhydrous ethanol solvent: 360-440 parts; 2-[(thiophene-2-ylmethoxy)methyl]ethylene oxide: 0.54-1.08 parts; 20-25% anhydrous dilute ammonia: appropriate amount (adjust pH to 7.0-8.0);
[0013] • S1. Add the above-mentioned lithium sulfide Li2S, phosphorus sulfide P2S5, tin sulfide SnS2, lithium chloride LiCl, phosphorus pentoxide P2O5, and niobium pentoxide Nb2O5 to anhydrous ethanol solvent respectively, and stir at 450-550 rpm for 25-35 minutes to make the raw materials initially uniformly dispersed.
[0014] • S2. Add EDTA and 2-[(thiophene-2-ylmethoxy)methyl]ethylene oxide, and stir in an oil bath at 55-65°C for 0.8-1.2 hours until the system is converted into a homogeneous transparent sol;
[0015] • S3. Slowly add anhydrous dilute ammonia to adjust the pH of the system to 7.0-8.0, and continue stirring for 1.8-2.2 hours to form a stable coordination sol that does not separate into layers and has no precipitate. Adjusting the pH value to create a suitable weakly alkaline environment is beneficial for the full progress of the metal ion coordination reaction and ensures the long-term storage stability of the sol.
[0016] The prepared stable coordination sol was transferred to a vacuum drying oven and dried at 60-80℃ to completely remove the anhydrous ethanol solvent, yielding a dry gel powder. The dry gel was then poured into a ball mill jar, sealed, and ball-milled for 0.5-2 hours at a speed of 400-600 rpm. Ball milling further refines the particles, resulting in a more uniform mixture of various precursor materials. The ball-milled material was then sealed in a vacuum quartz tube under a constant high-purity argon atmosphere. Annealing was performed at 500-600℃ for 5-10 hours at a heating rate of 2-4℃ / min. This annealing process eliminates internal stress defects and regularizes the crystalline precursor structure. After annealing, the quartz tube was transferred to an argon-filled tube muffle furnace for high-temperature solid-state sintering. Finally, the sintered electrolyte block was thoroughly ground using an agate mortar and pestle for 10-20 minutes to obtain an ultrafine electrolyte powder for later use.
[0017] As a preferred technical solution of the present invention, in step (1), the ball milling time is 0.5~2h and the ball milling speed is 400-600rpm.
[0018] As a preferred technical solution of the present invention, in step (1), the ball-milled sample is annealed at 500-600℃ for 5-10h under argon protection, with a heating rate of 2-4℃ / min.
[0019] As a preferred technical solution of the present invention, in step (1), the grinding time of the electrolyte after sintering is controlled to be 10-20 min.
[0020] As a preferred technical solution of the present invention, in step (2), the amount of electrolyte powder added to the mold at one time is 100-300mg.
[0021] As a preferred technical solution of the present invention, in step (2), the electrolyte powder is cold-pressed at a pressure of 300-400 MPa and held for 1-10 min.
[0022] As a preferred technical solution of the present invention, in step (2), after the electrolyte sheet clamps the lithium sheet, it is pressurized again by 30-60MPa, and the battery is packaged by maintaining the pressure.
[0023] Reaction mechanism:
[0024] In the preparation of anhydrous coordination sols, EDTA organic ligands can react with soluble metal ions (Li⁺, Sn⁻) in the system. 4 (e.g., ⁺) undergo chelation coordination reactions to form stable metal complexes, preventing the aggregation of metal precursor particles; Nb₂O₅ undergoes trace dissociation in a weakly alkaline anhydrous ethanol system, releasing Nb 5 + Forms stable Nb-based coordination units with EDTA, achieving uniform dispersion of niobium; 2-[(thiophene-2-ylmethoxy)methyl]ethylene oxide undergoes ring-opening crosslinking of epoxy groups under heating conditions of 55~65℃, with molecular chains intertwining to form a three-dimensional organic sol network, uniformly binding all metal precursors within the network structure. After adjusting the pH to 7.0~8.0 with anhydrous dilute ammonia, the coordination reaction of the system becomes more complete, the stability of the sol structure is greatly improved, and no water is introduced throughout the process, completely avoiding the side reaction of sulfide hydrolysis.
[0025] The vacuum drying process completely removes the ethanol organic solvent, retaining an atomically uniformly dispersed dry gel precursor; the medium-temperature annealing process removes organic ligands and simultaneously eliminates internal stress in the powder, initially forming the crystal framework of the doped precursor; during the high-temperature argon sintering stage, Li2S, P2S5, SnS2, Nb2O5, LiCl, and P2O5 undergo solid-phase atomic diffusion and lattice reconstruction, while Nb... 5 + Replace Li 10 SnP2S 12 Some P sites in the crystal lattice, O 2⁻Simultaneous replacement of the corresponding S site generates the target Li 10 SnP 2-X Nb x S 12- 2.5X O 2.5X The dual-doped crystal structure is achieved by co-doping with Nb and O to moderately expand the lattice gaps and construct a continuous three-dimensional lithium-ion transport channel. At the same time, ball milling refines the grains and reduces the grain boundary conduction impedance, thereby significantly improving the electrolyte ionic conductivity at the bulk level.
[0026] The beneficial effects of this invention: This invention, by defining a limited anhydrous sol preparation system, precisely controlling the Nb / O dual-doping ratio, and employing a segmented heat treatment process, prepares Li... 10 SnP 2-X Nb x S 12-2.5X O 2.5X Sulfide solid electrolytes have the following advantages:
[0027] Ultra-high lithium-ion conductivity: Anhydrous coordination sol achieves atomic-level uniform doping of Nb and O, and moderate lattice expansion broadens Li⁺ diffusion channels; ball milling and segmented annealing refine the grains, reducing grain boundary conduction resistance, resulting in electrolyte room-temperature ionic conductivity higher than undoped Li⁺. 10 SnP2S 12 The matrix was significantly improved;
[0028] Excellent moisture and thermal stability: O element doping modifies the surface lattice of the electrolyte, inhibiting the decomposition reaction of sulfides in water, and significantly improving the stability of the material when exposed to air; annealing results in a regular crystal structure with few internal stress defects, and no significant attenuation of electrochemical performance over a wide temperature range;
[0029] Excellent lithium metal interface compatibility: The uniform dual-doped system can effectively suppress the redox side reaction between the electrolyte and the lithium metal anode, and generate a thin and dense stable interface passivation layer in situ during long cycles, which greatly extends the cycle life of lithium symmetric batteries.
[0030] The process is safe and controllable: the entire process is prepared in an anhydrous inert atmosphere, which completely eliminates the generation of toxic H2S from sulfide hydrolysis; the heat treatment parameter window is wide, the operation is simple, and it has the potential for mass production.
[0031] The co-doping of Nb and O increases the lattice volume and widens the continuous diffusion channels of Li⁺, effectively improving the bulk ionic conductivity of the electrolyte from the crystal structure level. The accompanying anhydrous sol-coupled solid-state sintering process achieves uniform dispersion of dopants, further reducing interfacial side reactions and improving battery cycle life. Detailed Implementation
[0032] In this invention, the doping coefficient x ranges from 0.05 to 0.3. All raw material weighing, sol preparation, ball milling, tablet pressing, and battery assembly processes are completed in an argon glove box with a water and oxygen content of <0.1 ppm. Annealing and sintering are carried out entirely under the protection of a high-purity argon tubular furnace. All lithium symmetric batteries are operated at 0.1 mA·cm⁻ 2 Test the cycle stability time under constant current density.
[0033] Example 1
[0034] A Li 10 SnP 2-X Nb x S 12-2.5X O 2.5X The preparation method of sulfide solid-state battery includes the following steps: (1) Preparation of solid electrolyte: Solid electrolyte is prepared by anhydrous coordination sol-solid phase coupling sintering method. 229g lithium sulfide Li2S, 208g phosphorus sulfide P2S5, 182g tin sulfide SnS2, 2.1g niobium pentoxide Nb2O5, appropriate amount of lithium chloride LiCl, and phosphorus pentoxide P2O5 are used as initial raw materials to prepare stable anhydrous coordination sol. The preparation method of the stable coordination sol is as follows: ・Raw material ratio (mass): EDTA: 11 g; anhydrous ethanol solvent: 360 g; 2-[(thiophene-2-ylmethoxy)methyl]ethylene oxide: 0.54 g; 20% anhydrous dilute ammonia water: appropriate amount (adjust pH to 7.0). • S1. Add the above-mentioned lithium sulfide (Li2S), phosphorus sulfide (P2S5), tin sulfide (SnS2), niobium pentoxide (Nb2O5), lithium chloride (LiCl), and phosphorus pentoxide (P2O5) to anhydrous ethanol solvent, and stir at 450 rpm for 25 minutes to initially disperse the raw materials. • S2. Add EDTA and 2-[(thiophene-2-ylmethoxy)methyl]ethylene oxide, and stir in an oil bath at 55 °C for 0.8 hours until the system becomes a homogeneous sol. • S3. Add anhydrous dilute ammonia dropwise until the pH reaches 7.0, and continue stirring for 1.8 hours to form a stable coordination sol. Adjusting the pH value to maintain a suitable acid-base environment is beneficial for the coordination reaction and ensures the stability of the sol.
[0035] The prepared stable coordination sol was dried under vacuum at 70℃ for 6 hours to completely remove ethanol. The dried gel was poured into a ball mill jar, sealed, and ball-milled for 0.5 hours at a speed of 400 rpm. Ball milling further refines the particles and makes the raw materials more uniformly mixed. The ball-milled material was sealed in a quartz tube and annealed at 500℃ for 5 hours under argon protection at a heating rate of 2℃ / min. The annealing process can eliminate internal stress in the particles and improve the crystal structure. After annealing, the material was transferred to an argon-filled tube muffle furnace for high-temperature sintering. Finally, the sintered electrolyte was ground using an agate mortar and pestle for 10 minutes to obtain a fine electrolyte powder for later use.
[0036] (2) Preparation of lithium symmetric battery: In order to verify the compatibility between the electrolyte and lithium metal, a lithium symmetric battery was assembled and tested at 0.1 mA cm⁻. 2 The current density was subjected to constant current cycling tests. The preparation process included the following steps: First, in a glove box filled with argon gas, 100 mg of electrolyte powder was placed into a mold and pressed for 1 min under a pressure of 300 MPa. Then, the pressed electrolyte sheet was placed between two lithium sheets, and a pressure of 30 MPa was applied again for pressure holding and encapsulation, followed by electrochemical cycling tests. The current density at 0.1 mA cm⁻¹ was tested. 2 The cycling stability at the specified current density is 95 h.
[0037] Example 2
[0038] A Li 10 SnP2₋ x Nb x S 12 ₋2. 5x O2. 5x The preparation method of sulfide solid-state battery includes the following steps: (1) Preparation of solid electrolyte: Solid electrolyte is prepared by anhydrous coordination sol-solid coupling sintering method. 229.5g lithium sulfide Li2S, 215g phosphorus sulfide P2S5, 182.5g tin sulfide SnS2, 8g niobium pentoxide Nb2O5, appropriate amount of lithium chloride LiCl, and phosphorus pentoxide P2O5 are used as initial raw materials to prepare a stable anhydrous coordination sol.
[0039] The preparation method of the coordination sol is as follows: • Raw material ratio (mass): EDTA: 16 g; anhydrous ethanol solvent: 400 g; 2-[(thiophene-2-ylmethoxy)methyl]ethylene oxide: 0.8 g; 22% anhydrous dilute ammonia water: appropriate amount (to adjust pH to 7.5). • S1. Add the above-mentioned lithium sulfide Li2S, phosphorus sulfide P2S5, tin sulfide SnS2, niobium pentoxide Nb2O5, lithium chloride LiCl, and phosphorus pentoxide P2O5 to the anhydrous ethanol solvent respectively, and stir at 500 rpm for 30 minutes to initially disperse the raw materials. • S2. Add EDTA and 2-[(thiophene-2-ylmethoxy)methyl]ethylene oxide, and stir in an oil bath at 60℃ for 1 hour to transform the system into a homogeneous sol. • S3. Add anhydrous dilute ammonia dropwise until pH = 7.5, and continue stirring for 2.0 hours to form a stable coordination sol. Adjusting the pH value to maintain a suitable acid-base environment is beneficial for the coordination reaction and ensures the stability of the sol.
[0040] The prepared stable coordination sol was dried under vacuum at 70℃ for 8 hours to remove all solvent. The dried gel was poured into a ball mill jar, sealed, and ball-milled for 1 hour at 500 rpm. Ball milling further refines the particles and makes the raw materials more uniformly mixed. The ball-milled material was sealed in a quartz tube and annealed at 550℃ for 7 hours under argon protection with a heating rate of 3℃ / min. The annealing process eliminates internal stress in the particles and improves the crystal structure. After annealing, the electrolyte was sintered in a tube furnace. Finally, the sintered electrolyte was ground using an agate mortar and pestle for 15 minutes to obtain a fine powder for later use.
[0041] (2) Preparation of lithium symmetric battery: In order to verify the compatibility between the electrolyte and lithium metal, a lithium symmetric battery was assembled and tested at 0.1 mA cm⁻. 2 The current density was tested. The preparation process included the following steps: First, in a glove box filled with argon gas, 200 mg of electrolyte powder was placed into a mold and pressed for 5 minutes under a pressure of 350 MPa. Then, the pressed electrolyte sheet was placed between two lithium sheets, and a pressure of 50 MPa was applied again for pressure holding and encapsulation testing. Its current density at 0.1 mA cm⁻¹ was tested. 2 The cycling stability at the current density is 165h.
[0042] Example 3
[0043] A Li 10 SnP2₋ x Nb x S 12 ₋2.5x O2. 5x The preparation method of sulfide solid-state battery includes the following steps: (1) Preparation of solid electrolyte: Solid electrolyte is prepared by anhydrous coordination sol-solid coupling sintering method. 230g lithium sulfide Li2S, 222g phosphorus sulfide P2S5, 183g tin sulfide SnS2, 15.9g niobium pentoxide Nb2O5, appropriate amount of lithium chloride LiCl, and phosphorus pentoxide P2O5 are used as initial raw materials to prepare a stable anhydrous coordination sol.
[0044] The preparation method of the coordination sol is as follows: • Raw material ratio (mass): EDTA: 23 g; anhydrous ethanol solvent: 440 g; 2-[(thiophene-2-ylmethoxy)methyl]ethylene oxide: 1.08 g; 25% anhydrous dilute ammonia water: appropriate amount (to adjust pH to 8.0). • S1. Add the above-mentioned lithium sulfide Li2S, phosphorus sulfide P2S5, tin sulfide SnS2, niobium pentoxide Nb2O5, lithium chloride LiCl, and phosphorus pentoxide P2O5 to the anhydrous ethanol solvent respectively, and stir at 550 rpm for 35 minutes to initially disperse the raw materials. • S2. Add EDTA and 2-[(thiophene-2-ylmethoxy)methyl]ethylene oxide, and stir in an oil bath at 65℃ for 1.2 hours until the system transforms into a homogeneous sol. • S3. Add anhydrous dilute ammonia dropwise until pH = 8.0, and continue stirring for 2.2 hours to form a stable coordination sol. Adjusting the pH value to maintain a suitable acid-base environment is beneficial for the coordination reaction and ensures the stability of the sol.
[0045] The prepared stable coordination sol was dried under vacuum at 80℃ for 10 hours to completely remove the solvent. The dried gel was poured into a ball mill jar, sealed, and ball-milled for 2 hours at 600 rpm. Ball milling further refines the particles and makes the raw materials more uniformly mixed. The ball-milled material was sealed in a quartz tube and annealed at 600℃ for 10 hours under argon protection with a heating rate of 4℃ / min. The annealing process eliminates internal stress in the particles and improves the crystal structure. After annealing, the electrolyte was sintered in a tube furnace. Finally, the sintered electrolyte was ground using an agate mortar and pestle for 20 minutes to obtain a fine powder for later use.
[0046] (2) Preparation of lithium symmetric battery: In order to verify the compatibility between the electrolyte and lithium metal, a lithium symmetric battery was assembled and tested at 0.1 mA cm⁻. 2The current density was tested. The preparation process included the following steps: First, in a glove box filled with argon gas, 300 mg of electrolyte powder was placed into a mold and pressed for 10 minutes under a pressure of 400 MPa. Then, the pressed electrolyte sheet was placed between two lithium sheets, and a pressure of 60 MPa was applied again for pressure holding and encapsulation testing. Its current density at 0.1 mA cm⁻¹ was tested. 2 The cycling stability at the specified current density is 205 h.
[0047] Comparative Example 1
[0048] A Li 10 SnP2S 12 The preparation method of sulfide solid-state battery includes the following steps: (1) Preparation of solid electrolyte: Solid electrolyte is prepared by traditional direct solid-state ball milling sintering method. 229g of lithium sulfide Li2S, 208g of phosphorus sulfide P2S5 and 182g of tin sulfide SnS2 powder are directly mixed without adding Nb2O5 and without preparing coordination sol; the mixed powder is poured into a ball mill jar and sealed, and placed in a ball mill for ball milling at a speed of 400rpm for 0.5h. Finally, the ball-milled material is sealed in a quartz tube and sintered at 500℃ for 5h in an argon tube furnace at a heating rate of 2℃ / min. The sintered electrolyte is then ground for 10min and set aside for later use.
[0049] (2) Preparation of lithium symmetric battery: In order to verify the compatibility between the electrolyte and lithium metal, a lithium symmetric battery was assembled and tested at 0.1 mA cm⁻. 2 The current density was tested. The preparation process included the following steps: First, in a glove box filled with argon gas, 100 mg of electrolyte powder was placed into a mold and pressed for 1 minute under a pressure of 300 MPa. Then, the pressed electrolyte sheet was placed between two lithium sheets, and a pressure of 30 MPa was applied again for pressure holding and encapsulation testing. Its current density at 0.1 mA cm⁻¹ was tested. 2 The cycling stability at the specified current density is 50 h.
[0050] Comparative Example 2
[0051] A Li 10 SnP 2-x Nb x S 12-2.5x O 2.5xThe preparation method of sulfide solid-state battery includes the following steps: (1) Preparation of solid electrolyte: The direct solid-state ball milling sintering method is adopted without the coordination sol preparation process. 229.5g of lithium sulfide Li2S, 215g of phosphorus sulfide P2S5, 182.5g of tin sulfide SnS2, and 8g of niobium pentoxide Nb2O5 are used as initial raw materials and directly physically mixed, poured into a ball mill jar and sealed, and placed in a ball mill for ball milling. The speed is set to 500rpm and the ball milling time is 1h. Finally, the ball-milled material is sealed in a quartz tube and sintered in an argon tube furnace at 550℃ for 8h with a heating rate of 3℃ / min. The sintered electrolyte is then ground for 10min and set aside for later use.
[0052] (2) Preparation of lithium symmetric battery: In order to verify the compatibility between the electrolyte and lithium metal, a lithium symmetric battery was assembled and tested at 0.1 mA cm⁻. 2 The current density was tested. The preparation process included the following steps: First, in a glove box filled with argon gas, 200 mg of electrolyte powder was placed into a mold and pressed for 5 minutes under a pressure of 350 MPa. Then, the pressed electrolyte sheet was placed between two lithium sheets, and a pressure of 50 MPa was applied again for pressure holding and encapsulation testing. Its current density at 0.1 mA cm⁻¹ was tested. 2 The cycling stability at the specified current density is 70 h.
[0053] Table 1. Comparison of process conditions and electrochemical performance of each example and comparative example (test conditions: 0.1 mA·cm⁻) 2 (room temperature)
[0054] Group Is it Nb / O double doped? Is anhydrous sol-gel process used? Annealing temperature / °C Cold pressing pressure / MPa Stable cycle time of lithium symmetric battery / h Performance Description Comparative Example 1 no no 500 300 50 Undoped, sol-free, pure matrix, with the worst cycle life. Comparative Example 2 yes no 550 350 70 Only Nb / O doping, with uniform dispersion without sol, results in a slight performance improvement. Example 1 yes yes 500 300 95 Low doping level + complete sol-gel process, outperforming the two comparative groups. Example 2 yes yes 550 350 165 Medium doping level, optimized process parameters, and significantly improved cycle life Example 3 yes yes 600 400 205 Maximum doping level, complete gradient heat treatment, optimal cycle stability
[0055] The following conclusions can be clearly drawn from the performance comparison data in the table above:
[0056] 1. Using only Nb and O double doping but without using the anhydrous coordination sol preparation process of this invention (Comparative Example 2), the cycle stability is only slightly improved compared to the undoped matrix (Comparative Example 1), indicating that simple physical mixing doping cannot achieve uniform element distribution and the doping modification effect is limited;
[0057] 2. Examples 1-3, which simultaneously employ Nb / O dual doping + anhydrous coordination sol coupled solid-state sintering process, show that the cycle time of lithium symmetric batteries is much longer than that of the two comparative examples. This proves that anhydrous coordination sol can achieve atomic-level uniform dispersion of Nb and O, fully leverage the lattice regulation effect of dual doping, and significantly improve the compatibility of the electrolyte and lithium metal interface.
[0058] 3. With the increase of Nb and O doping amount and the optimization of annealing temperature and molding pressure gradient, the cycle stability of the battery continues to improve. Example 3 achieved the optimal cycle life of 205h under the upper limit of the process parameters limited by the present invention.
[0059] 4. The anhydrous ethanol solvent system of this invention completely avoids the sulfide hydrolysis problem caused by traditional water-ethanol mixed solvents. The entire process is heat-treated with argon inert atmosphere to prevent electrolyte oxidation. Combined with segmented annealing to refine grains and reduce grain boundary resistance, it simultaneously improves electrolyte ionic conductivity, moisture stability and long cycle life.
[0060] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention. Process parameters, raw material ratios, equipment models, etc., not described in detail in this invention are all conventional technical means in the art, and can be flexibly adjusted by those skilled in the art according to actual production needs without creative effort, and all fall within the protection scope defined by the claims of this invention. The Li prepared by this invention... 10 SnP 2-x Nb x S 12-2.5x O 2.5x Sulfide solid electrolytes can be widely used in electrochemical energy storage devices such as all-solid-state lithium batteries, solid-state energy storage batteries, and micro solid-state power supplies, and have good prospects for industrialization and economic value.
Claims
1. A Li 10 SnP2₋ x Nb x S 12 ₋2. 5x O2. 5x A method for preparing a sulfide solid-state battery, characterized in that, Includes the following steps: (1) Preparation of solid electrolyte: Solid electrolyte was prepared by solid-state sintering. Under the inert atmosphere of high-purity argon, lithium sulfide (Li2S), phosphorus sulfide (P2S5), tin sulfide (SnS2), and niobium pentoxide (Nb2O5) were used as core raw materials, and lithium chloride (LiCl) and phosphorus pentoxide (P2O5) were used as auxiliary agents to prepare a stable anhydrous coordination sol. (2) Preparation of lithium symmetric batteries: To verify the compatibility between the electrolyte and lithium metal, lithium symmetric batteries were assembled and tested at a certain current density. The preparation process included the following steps: First, in a glove box filled with argon gas, a certain pressure was applied to a suitable amount of electrolyte powder to press it. Then, the pressed electrolyte sheet was placed between two lithium sheets, pressure was applied again, and a pressure-holding electrochemical cycle test was performed to test its cycle stability.
2. A Li according to claim 1 10 SnP2₋ x Nb x S 12 ₋2. 5x O2. 5x A method for preparing a sulfide solid-state battery, characterized in that, In step (1), lithium sulfide (Li2S), phosphorus sulfide (P2S5), tin sulfide (SnS2), niobium pentoxide (Nb2O5), lithium chloride (LiCl), and phosphorus pentoxide (P2O5) are mixed together to prepare a stable coordination sol, which is protected by anhydrous and oxygen-free argon gas throughout the process.
3. A Li according to claim 1 10 SnP2₋ x Nb x S 12 ₋2. 5x O2. 5x A method for preparing a sulfide solid-state battery, characterized in that, In step (1), the preparation method of the coordination sol is as follows: • Raw material ratio (parts by weight): EDTA: 11-23 parts; anhydrous ethanol solvent: 360-440 parts; 2-[(thiophene-2-ylmethoxy)methyl]ethylene oxide: 0.54-1.08 parts; 20-25% anhydrous dilute ammonia: appropriate amount (to adjust pH to 7.0-8.0); • S1. Add the above-mentioned lithium sulfide Li2S, phosphorus sulfide P2S5, tin sulfide SnS2, lithium chloride LiCl, phosphorus pentoxide P2O5, and niobium pentoxide Nb2O5 to anhydrous ethanol solvent respectively, and stir at 450-550 rpm for 25-35 minutes to initially disperse the raw materials. • S2. Add EDTA and 2-[(thiophene-2-ylmethoxy)methyl]ethylene oxide, and stir in an oil bath at 55-65°C for 0.8-1.2 hours until the system transforms into a homogeneous sol; • S3. Add anhydrous dilute ammonia dropwise until the pH reaches 7.0-8.0, and continue stirring for 1.8-2.2 hours to form a stable coordination sol. Adjusting the pH value to maintain a suitable acid-base environment is beneficial for the coordination reaction and ensures the stability of the sol. Transfer the prepared stable coordination sol to a vacuum drying oven at 60-80℃ to completely remove the solvent. After drying, pour the dried gel into a ball mill jar, seal it, and place it in a ball mill for 0.5-2 hours at a speed of 400-600 rpm. Ball milling further refines the particles and makes the raw materials more uniformly mixed. The ball-milled material is sealed in a quartz tube under argon protection throughout the process. It is first annealed at 500-600℃ for 5-10 hours with a heating rate of 2-4℃ / min. The annealing process can eliminate the internal stress of the particles and improve the crystal structure. After annealing, it is transferred to an argon tube muffle furnace for high-temperature sintering. Finally, the electrolyte obtained by sintering is ground using an agate mortar and pestle for 10-20 minutes to obtain a fine powder for later use.
4. A Li according to claim 3 10 SnP2₋ x Nb x S 12 ₋2. 5x O2. 5x A method for preparing a sulfide solid-state battery, characterized in that, The ball milling time is 0.5~2 hours, and the ball milling speed is 400-600 rpm.
5. A Li according to claim 3 10 SnP2₋ x Nb x S 12 ₋2. 5x O2. 5x A method for preparing a sulfide solid-state battery, characterized in that, After ball milling, the material is annealed at 500-600℃ for 5-10 hours, with a heating rate of 2-4℃ / min, under an argon atmosphere.
6. A Li according to claim 3 10 SnP2₋ x Nb x S 12 ₋2. 5x O2. 5x A method for preparing a sulfide solid-state battery, characterized in that, The electrolyte grinding time after sintering is 10-20 min.
7. A Li according to claim 1 10 SnP2₋ x Nb x S 12 ₋2. 5x O2. 5x A method for preparing a sulfide solid-state battery, characterized in that, In step (2), the amount of electrolyte powder placed into the mold is 100-300 mg.
8. A Li according to claim 1 10 SnP2₋ x Nb x S 12 ₋2. 5x O2. 5x A method for preparing a sulfide solid-state battery, characterized in that, In step (2), the electrolyte powder is kept under a pressure of 300-400 MPa for 1-10 minutes.
9. A Li according to claim 1 10 SnP2₋ x Nb x S 12 ₋2. 5x O2. 5x A method for preparing a sulfide solid-state battery, characterized in that, In step (2), the pressed electrolyte sheet is placed between two lithium sheets, and a pressure of 30-60 MPa is applied again and pressure is maintained and sealed. Then, an electrochemical cycle test is carried out.
